Memperkuat minat literasi anak usia dini melalui kegiatan membaca Alkitab - Alfan Ghafar; Sonya Kusuma Putri (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
The aim of this research is to determine interest in reading and writing in young children through reading the Holy Bible. This research uses a library research method (Library Research) which aims to determine the influence of reading the Holy Bible in early childhood on interest in reading. The important role of parents in forming the foundation of spiritual knowledge. The family is a place where children experience mental, physical, emotional and social growth. A Christian family is a family that makes Christ the foundation and strong foundation of its family.